The Influence of Cash Turnover, Accounts Receivable Turnover, Capital Structure, and Profit Growth on Profitability - Azizah Nasya Ziyadatul; Dewi Siska; Rokhman Nur (SHS Web of Conferences)
In this empirical study of manufacturing businesses in the consumer products industrial sector listed on the IDX in 2019–2023, the impact of cash turnover, receivables turnover, capital structure, and profit growth on profitability is the main goal. Purposive sampling was the approach utilized to choose the sample for this study. Secondary data from the Indonesia Stock Exchange (IDX) is the sort of data that was used. Multiple linear regression analysis using SPSS version 25 is the method employed. The findings of the partial study indicate that while cash turnover has no discernible impact on profitability, the turnover of receivables, capital structure, and profit growth do. Concurrently, the findings demonstrate that profitability is impacted by cash turnover, receivables turnover, capital structure, and profit growth.